2019
DOI: 10.21577/0103-5053.20190117
|View full text |Cite
|
Sign up to set email alerts
|

Uncured Polydimethylsiloxane as Binder Agent for Carbon Paste Electrodes: Application to the Quantification of Propranolol

Abstract: This study describes the use of uncured polydimethylsiloxane (PDMS) as a binder agent to prepare carbon paste electrodes (CPEs). A comparative study between the properties of CPEs prepared with PDMS and mineral oil Nujol ® , the most common binder agent for CPEs, was carried out. Cyclic voltammetry, electrochemical impedance spectroscopy, and chronoamperometry showed that PDMS-CPEs presented higher electrical conductivity, active electrochemical area, and wider useful potential window compared with Nujol ®-CPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(67 reference statements)
1
3
0
Order By: Relevance
“…Table S3 shows the electrochemical responses of the composites from the same batch were reproducible (RSD = 10%) since the sensitivities of the sensors were not significantly compromised by using different electrodes. RSD close to this estimated value was reported in the literature for other types of carbon composites, 1,8,26,45,46 demonstrating the proposed material has acceptable reproducibility. The batch‐to‐batch reproducibility was poorer (RSD = 15%).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Table S3 shows the electrochemical responses of the composites from the same batch were reproducible (RSD = 10%) since the sensitivities of the sensors were not significantly compromised by using different electrodes. RSD close to this estimated value was reported in the literature for other types of carbon composites, 1,8,26,45,46 demonstrating the proposed material has acceptable reproducibility. The batch‐to‐batch reproducibility was poorer (RSD = 15%).…”
Section: Resultssupporting
confidence: 85%
“…Carbon composites are widely used for numerous applications including chemical sensors, 1 supercapacitors, 2 and fuel cells 3 . The carbon paste electrodes are one of the main carbon composites used for electroanalytical applications 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, it exhibited superior signal-to-noise ratios and demonstrated enhanced electrochemical activity when compared to the conventional carbon paste electrode, which relied solely on paraffin oil as the binder. The research outlined in [29] detailed the utilization of uncured polydimethylsiloxane (PDMS) as a binding agent in the construction of carbon paste electrodes. The investigation demonstrated that PDMS stands out as a promising alternative binder, characterized by enhanced chemical and electrochemical stability, leading to improved analytical performance.…”
Section: Introductionmentioning
confidence: 99%